Please, marry me!: An experimental study of risking a joint venture - Werner Güth; Radosveta Ivanova-Stenzel; Sigve Tjotta (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
Empirical studies in family economics usually rely on questionnaires, statistical or panel data. Here we try to study experimentally some crucial aspects of engaging in a marriage. First the female partner can end the relationship or suggest one of the two forms of joint venture. Whereas a full engagement relies on more specialization, but makes her more exploitable by the male partner, a low engagement is less productive, but also fairer. More specifically, the random profit of a joint venture is allocated by ultimatum bargaining in case of a full engagement whereas demands are determined simultaneously in case of a low engagement. Partners interact anonymously. In the repetition the two partners in a matching group of four participants are exchanged. Our treatment variables are her and his outside option value representing gender specific investments in human capital.
urn:nbn:de:kobv:11-10046793
Keywords: 330